PEMANFAATAN ALAT PERMAINAN EDUKATIF BUNGA BERHITUNG DARI BARANG BEKAS DALAM MENGEMBANGKAN KEMAMPUAN KOGNITIF ANAK USIA DINI DI TK MARDISIWI - Faida, Dyna Nur; Pascalian Hadi Pradana; Nurhafit Kurniawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the use of the Counting Flower Educational Play Tool (APE), made from recycled materials, in developing the cognitive abilities of early childhood learners at TK Mardisiwi, Kalibaru Wetan, Banyuwangi. Cognitive ability is a crucial aspect of children's intellectual development, including number recognition, color differentiation, counting, and basic problem-solving. The research employs a qualitative descriptive method with data collected through observation, interviews, and documentation. The findings show that the use of the Counting Flower tool increases children's enthusiasm, enhances their understanding of basic mathematical concepts, and encourages engaging and interactive learning. Teachers found the tool helpful due to its simplicity, attractiveness, and affordability as it is made from reused materials. Moreover, the tool instills values of creativity and environmental awareness in children. This study recommends the use of creative and eco-friendly learning media as an effective alternative in early childhood education.